UPLC-Q-TOF-MS, Network Pharmacology and Molecular Docking to Reveal the Antidepressant Mechanism of the Different Components of Medicinal and Edible Lilies (Lilium sp. pl) - Tan, Zhaoyang; Huang, Linghe; Tian, Yanqiu; Jiang, Sai; Wang, Zhi; Long, Hongping; Tong, Qiaozhen; Li, Shunxiang; Jiang, Lin (Combinatorial Chemistry & High Throughput Screening, 2025)
<span class=
Keywords: depression